Fabrication of micro dimples pattern using ball end mill - Muhamad Izdhar, Zaki; Saptaji, Kushendarsyah; Ramdan, R. D.; Kurniawan, Tedi (IOP Publishing, 2019)
In this paper, the effect of workpiece tilt angle and feed direction in producing micro dimple pattern using ball end mill tools were studied. Experiments were conducted using carbide ball end mill tools, aluminium Al 6061-T6 workpiece and using CNC machine. Three workpiece tilt angles are selected 00, 300 and 450; and two feed directions z-axis and x-axis. Visual observations using Scanning Electron Microscope (SEM) and geometry measurements using laser scanning confocal microscope were conducted on the fabricated micro dimple patterns. The results show that the workpiece tilt angle produces less burr at the edge of the dimples compared to without tilt (00). In addition, the workpiece tilt angle can avoid the formation of undercut at the center of the dimple. The workpiece tilt angle of 300 and z-axis feed direction produced better result compared to 00 and 450 tilt angles with the value of ratio diameter/depth closer to the theoretical value.